Lung cancer patients with COVID-19 in Spain: GRAVID study. (July 2021) - Provencio, Mariano; Mazarico Gallego, José María; Calles, Antonio; Antoñanzas, Mónica; Pangua, Cristina; Mielgo Rubio, Xabier; Nadal, Ernest; Castro, Rafael López; López-Martín, Ana; del Barco, Edel; Dómine, Manuel; Franco, Fernando; et al.
Highlights: GRAVID reports one of the largest series of patients with lung cancer and COVID-19. Of 447 patients, 78 % were hospitalized, 2% were admitted to ICU and 33 % died. Mortality was higher in patients who received corticosteroids at hospitalization. Anticancer therapy was not associated with increased risk of death. Individual risks and benefits should be considered in management of these patients. Abstract: Introduction: Patients with cancer may be at increased risk of more severe COVID-19 disease; however, prognostic factors are not yet clearly identified. The GRAVID study aimed to describe clinical characteristics, outcomes, and predictors of poor outcome in patients with lung cancer and COVID-19. Methods: Prospective observational study that included medical records of patients with lung cancer and PCR-confirmed COVID-19 diagnosis across 65 Spanish hospitals. The primary endpoint was all-cause mortality; secondary endpoints were hospitalization and admission to intensive care units (ICU). Results: A total of 447 patients with a mean age of 67.1 ± 9.8 years were analysed. The majority were men (74.3 %) and current/former smokers (85.7 %). NSCLC was the most frequent type of cancer (84.5 %), mainly as adenocarcinoma (51.0 %), and stage III metastatic or unresectable disease (79.2 %). Nearly 60 % of patients were receiving anticancer treatment, mostly first-line chemotherapy. Overall, 350 (78.3 %) patients were hospitalized for a mean of 13.4 ± 11.4 days, 9 (2.0 %) were admitted to ICU and 146 (32.7 %) died. Advanced disease and the use of corticosteroids to treat COVID-19 during hospitalization were predictors of mortality. Hospitalized, non-end-of-life stage patients with lymphocytopenia and high LDH had an increased risk of death. Severity of COVID-19 correlated to higher mortality, ICU admission, and mechanical ventilation rates. Conclusions: Mortality rate was higher among patients treated with corticosteroids during hospitalization, while anticancer therapy was not associated with an increased risk of hospitalization or death. Tailored approaches are warranted to ensure effective cancer management while minimizing the risk of exposure to SARS-CoV-2.